Wildfire ocurrence in La Pampa Province, Argentina (2005-2017) (Semiárida, 2024)
Fire is a natural component of ecosystems as well as a management tool in agricultural systems in the province of La Pampa. Nevertheless, forest and rural fires also represent a risk to people, properties, rural activities and natural resources. The objective of this work was to examine wildfire occurrence in La Pampa between the years 2005 and 2017.  The number and causes of fires, the burnt area and type of vegetation affected were examined for each of the 22 Departments and for the province. 638 events were recorded during the study period affecting a total of 2,675,875 hectares (about 18.7 % of the province). The majority of the events were of natural origin, not exceeded 5,000 hectares in area and affected in similar proportions, native forests, shrublands and grasslands. Most fires burned during January, probably due to conditions of higher temperature, low fuel humidity, and the occurrence of electrical storms that favor fire ignition and spread. The most significant season was 2016/17 with 1,337,170 hectares affected. Among the Departments, Chalileo and Caleu Caleu had the largest burned area (˃570,000 hectares; ~65 % of total surface); while Chalileo and Utracán presented the highest number of fires (~115). Meanwhile, no fires were recorded in the northeastern sector of the province. These results contribute to the prevention and planning activities developed for fire risk management at the provincial and regional level.
Keywords: wildfire; calden forest; rangelands; monte; wildfire risk